If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 = -1.8 Reorder the terms: -7 + 2x = -1.8 Solving -7 + 2x = -1.8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2x = -1.8 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -1.8 + 7 2x = -1.8 + 7 Combine like terms: -1.8 + 7 = 5.2 2x = 5.2 Divide each side by '2'. x = 2.6 Simplifying x = 2.6
| 8x-3=9.8 | | 7-6=2x | | (3^-7/3^-10)*3^-5+5 | | 3lnx=0 | | 15x+10y=-30 | | 39+u=85 | | 6r-7=29 | | 5a+5=3a+19 | | 2j-10=-16 | | 2^5x3^4/2^7x3^2 | | y-10=-2 | | y+5=-3 | | [-30(-7)]-[210(-3)]= | | (-2)(3)(-5)= | | x^2=4/8 | | 81/-9 | | -54/-6 | | -72+-24= | | x^2-9/16 | | 19-(-3)= | | 4(x+1.52)=3x | | 0.01x/2=9 | | 3.4x-86=1.9x+7 | | sin(2x)=.8 | | 4x+84=291-3x | | Y-2.7=6 | | 6-=4 | | x/6+17=22 | | x/17+82=88 | | x/5=97-17 | | 3x+15=175-2x | | 4x-38=42-4x |